A practical model for embodied coaching. Issue 1 (2nd January 2018) - Attan, Anthony; Whitelaw, Ginny; Ferguson, Emily
ABSTRACT: Coaches often seek ways to support their coachees in making behavioural shifts as they work towards desired outcomes. Some approaches to coaching focus on the use of feedback and personality assessments to increase self-awareness, but are limited in supporting change. Other approaches emphasise somatic elements, for example, in the embodiment of habits and the connection to self-regulation, but do not connect to an integrated model of personality. This paper gives evidence for a practical framework for embodied coaching that combines the best of both, integrating mind and body and connecting self-awareness of personality to self-regulation towards desired outcomes. We demonstrate the validity of this framework through: (1) psychometric validation of an assessment connecting four movement patterns to four factors of personality and (2) a study showing how movement in each pattern gives rise to four distinct psychological states. We explore applications of this model to support behavioural shifts and create successful coaching outcomes.